Dampak Mindfulness Based Stress Reduction (MBSR) terhadap Stress Ibu yang Mengasuh Anak Berkebutuhan Khusus (ABK) - Untari, Rita; Nugroho, Maharso Adhi; Hastuti, Siwi Dwi (Politeknik Kesehatan Kemenkes Surakarta, 2025)
Background: Stress is defined as a state of being pressured, both physically and psychologically. Stress experienced by mothers in raising children with special needs is called parenting stress. Mothers experience stress during the parenting process. Therefore, it is important to implement appropriate interventions. One form of intervention that can reduce stress is Mindfulness-Based Stress Reduction. Objectives: This study aims to examine the impact of Mindfulness-Based Stress Reduction (MBSR) on the stress of mothers of children with special needs (CWSN) at the Bunda Kirani Foundation in Boyolali. Methods: The research design is a quantitative, pre-experimental, one-group, pre-test and post-test design. The intervention using MBSR techniques includes body scanning, sitting meditation, hatha yoga, and walking meditation, with a total of 15 respondents. MBSR interventions were conducted 10 times. The measurement instrument used in this study was the Perceived. The assessment instrument used in this study was the Perceived Stress Scale. The sampling technique used was purposive sampling. The data analysis was performed using the Paired t-test. Results: The largest sample had a high school education background, totaling 9 people (60%), the majority were 38 years old, totaling 3 people (20%), and the oldest sample was 48 years old, totaling 1 person (6.7%). There was a decrease in scores, with an average of 5.34 after being given MBSR treatment. The hypothesis test showed a p-value of 0.000 (p < 0.05), indicating that there was a statistically significant effect of MBSR treatment on the stress of mothers who have children at Yayasan Bunda Kirani Boyolali. Conclusion: MBSR impacts the reduction of stress in mothers who have children with developmental disabilities and provides direct caregiving. Keywords : Children with special needs, Stress, Mindfulness, MBSR.